RELATIONSHIP BETWEEN SOIL HUMUS DISSIMILATION, SOIL BIOLOGICAL AND CHEMICAL PROPERTIES, AND LEAF LITTER CHARACTERISTICS IN PURE FORESTS - Zhang, Xiaoxi; Liu, Zengwen; Liu, Xiaobo; Liang, Xiao (Emirates Journal of Food and Agriculture, 2017)
Soil humus dissimilation in 8 kinds of pure forests was detected and its relationship with soil biological and chemical properties and leaf litter characteristics was assessed using partial least squares regression (PLS-R). The results indicated that: The particular soil properties in pure forest rather than the litter characteristics exhibited the dominant impacts on humus accumulation and degree of humifications. High soil microbial biomass carbon (MC), alkaline N and available P contents, soil phosphatase, dehydrogenase and urease activities, and litter accumulation were associated with high humic acid accumulation, while high soil available Fe and litter Mn contents were opposite. High soil MC, alkaline N, available Zn and P contents, and dehydrogenase and phosphatase activities were in favour of fulvic acid accumulation, while the high litter Mn content were opposite. High soil MC and alkaline N contents, dehydrogenase and phosphatase activities and high litter N content were associated with the accumulation of humin, in contrast, increase in soil available K and Zn contents and sucrase activity hindered this process. Increases in soil available K content, urease and peroxidase activities and litter accumulation and C/P ratio increased the degree of humifications of soil, while the increases in soil available Fe and Cu contents, catalase activity and litter P content significantly decreased it.